2016
DOI: 10.1007/s11095-016-1961-x
|View full text |Cite
|
Sign up to set email alerts
|

The Mystery of Antibodies Against Polyethylene Glycol (PEG) - What do we Know?

Abstract: We confirm that some healthy individuals and some patients with hemophilia express specific antibodies against PEG which are not associated with any pathology and do not bind to human tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 43 publications
3
83
4
2
Order By: Relevance
“…PEG was long considered to be nonimmunogenic, but recent reports show that anti-PEG antibodies can be induced by injection of some types of pegylated liposomes or proteins in clinical trials [6][7][8][9][10][11][12][13][14] and animal studies [15][16][17][18][19][20][21][22][23][24]. Although anti-PEG antibodies do not appear to be induced when most pegylated human proteins are administered to patients, a large proportion of the general population never exposed to pegylated drugs has pre-existing anti-PEG antibodies in their circulation, possibly due to widespread exposure to PEG in commonly used products such as cosmetics, soaps, and medicines [10][11][12]16,[25][26][27][28][29][30][31]. For example, we recently found that over 40% of 1504 normal donors had measurable anti-PEG IgM and IgG antibodies in their plasma [25].…”
Section: Introductionmentioning
confidence: 99%
“…PEG was long considered to be nonimmunogenic, but recent reports show that anti-PEG antibodies can be induced by injection of some types of pegylated liposomes or proteins in clinical trials [6][7][8][9][10][11][12][13][14] and animal studies [15][16][17][18][19][20][21][22][23][24]. Although anti-PEG antibodies do not appear to be induced when most pegylated human proteins are administered to patients, a large proportion of the general population never exposed to pegylated drugs has pre-existing anti-PEG antibodies in their circulation, possibly due to widespread exposure to PEG in commonly used products such as cosmetics, soaps, and medicines [10][11][12]16,[25][26][27][28][29][30][31]. For example, we recently found that over 40% of 1504 normal donors had measurable anti-PEG IgM and IgG antibodies in their plasma [25].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that low levels of anti-PEG antibodies are detectable in the plasma of 47 to 72% of patients, irrespective of the collection date. Parallel studies in healthy donors without prior exposure to PEGylated therapeutics living in Austria, the US and Taiwan also show that anti-PEG immunoglobulins are present in 20 to 44% of blood samples [21,22]. Recently, a genome-wide association study conducted in patients from Taiwan identified the immunoglobulin heavy chain locus as a site of genetic variation that could predispose to the development of anti-PEG IgMs [23].…”
mentioning
confidence: 98%
“…[11,14,15] Despite the broad applicability of PLL-g-PEG films, several drawbacks have been associated with the application of PEG derivatives,i ncluding their tendency to undergo oxidative degradation to yield toxic compounds, [16,17] and the expression of antibodies specific for PEGs in vivo. [18][19][20] Appropriate alternatives that display improved chemical stability would be highly desirable,while polymers presenting more easily tailorable chemistries would give access to alarger variety of functional surfaces.…”
mentioning
confidence: 99%